Allium ursinum L. in Germany – surprisingly low genetic variability. Issue 1 (9th January 2013) - Herden, Tobias; Neuffer, Barbara; Friesen, Nikolai
Abstract: Allium ursinum s.l. is a widely spread species of the herb layer in beech forests throughout Europe. Little is known about its phylogenetic origin and its biogeographic history. Molecular genetic analyses of eleven populations from Germany were used to clarify the relationship between populations of A. ursinum s.l. and its relationship to several other species of the genus Allium . The study focused mainly on the Teutoburg Forest in Lower Saxony and the Franconian mountain area in Bavaria. Sequences of the nuclear internal transcribed spacer ITS, and the external transcribed spacer ETS, as well as the plastidic trn L ‐rpl 32 and the trn L‐ trn F spacer regions were compared. No variation was detected within the species. Even sequences of populations from Belfast, Ireland did not differ from populations of Germany. The closest relative to Allium ursinum s.l. turned out to be Allium moly or Allium scorzonerifolium from the section Molium . Random amplified polymorphic DNA fingerprinting was performed and revealed 29% polymorphic bands. Genetic distances of the populations within the Teutoburg Forest coincided with geographical distances. Three populations (Osnabrück Westerberg, Osnabrück Honeburg and Leer, East Frisia) out of eleven analysed populations were identified as garden escapes. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)